The effective factors on our early and late results, recurrence and survival in differential thyroid cancers: “An analysis of 184 patients” (Annals of Medical Research, 2021)
Aim: The purpose of the study was to investigate the effective prognostic factors on recurrence and mortality in patients with differential thyroid cancer. Material and Methods: The effects of various parameters of demographic characteristics, the admission symptoms, physical examination, laboratory findings, pathological examination, and surgical method of 184 patients, who underwent surgery due to differential thyroid cancer between January 1986 and December 2009 in 4th General Surgical Clinic of Ankara Numune Training and Research Hospital, on prognosis were examined. The information of the patients was obtained from automation system of the hospital and Thyroid Cancer Information and Follow-Up Form of 4th General Surgical Clinic of Ankara Numune Training and Research Hospital.Results: The sample group consisted of 172 papillary cancer patients and 12 follicular cancer patients. The mean age of the patients was 45.4 years (15-78). There were 159 (86.4%) female patients and 25 (13.6%) male patients. The mean follow-up period of 161 (87.5%) patients, who were followed up regularly, was 73.26 months (1-231). The mean recurrence period was 77.66 months (1-150). Mortality was observed in eight (4.3%) patients during their follow-up period. The mean life expectancy of those who died was 66.87 months (1-150 months).* Single variable analysis revealed that the T stage and pathologic final stage were effective on recurrence. Painful nodules and palpable lymph nodes in the neck and the papillary histological malignant subtype variant, as well as the presence of vascular and adjacent organ invasion, multicentricity, T stage, the lymph nodes, distant metastasis, and the clinical stage during the admission were identified to be effective on mortality.Conclusion: The risk of recurrence is high in DTC patients with high T stage and advanced pathologic stage. The rate of survival of those with multicentric tumors and advanced pathologic stage is low. Therefore, it is important for patients to be followed up closely within a postoperative multidisciplinary context.Keywords: Differential; thyroid; cancer; recurrence; mortality.
Keywords: Differential; thyroid; cancer; recurrence; mortality.